2005
DOI: 10.1292/jvms.67.877
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gender Differences in DBA/2Cr Mouse Kidney Morphology during Maturation

Abstract: ABSTRACT. Although we recently clarified sex-based differences in mouse kidney morphology, the developmental processes responsible for these gender differences during maturation remain unclear. The present study analyzed the morphometry of kidneys from 20-, 30-, 50-, 60-, 70-, 90-, 120-and 150-day-old DBA/2Cr mice. Total kidney weight and ratio of kidney weight to body weight were larger in males than females beginning at 50 days of age. The percentage of renal corpuscles exhibiting a cuboidal parietal layer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…Female mice in our study had a significantly lower kidney and body weight than males, consistent with observations from previous studies (18,28). Brain weight, as a proportion of total body weight, was greater in female than male mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Female mice in our study had a significantly lower kidney and body weight than males, consistent with observations from previous studies (18,28). Brain weight, as a proportion of total body weight, was greater in female than male mice.…”
Section: Discussionsupporting
confidence: 92%
“…Total glomerular volume and total renal corpuscle volume was also found to be greater in female than in male mice. Two previous studies investigated sex differences in glomerular morphology in mice at a similar age yet failed to detect sex differences in renal corpuscle diameter or glomerular area (18,28), although neither study employed unbiased stereological techniques. Okada et al (28) found no sex differences in cortical corpuscle diameter in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study illustrated degeneration of convoluted tubules with infl ammatory infi ltrate cells of the fetal kidney in the CBZ group. This data is in line with Okada's (2005) study results that showed CBZ can lead to degeneration of the renal tubules and atrophy of the glomeruli (22). Furthermore, Takayasu (2010) confi rmed that concentrations of CBZ metabolites are much higher in the kidney, liver, lung, and brain than in the blood.…”
Section: Discussionsupporting
confidence: 74%
“…The occurrence of cuboidal epithelium is influenced by gonadectomy, and as mice mature, the number of glomeruli with cuboidal epithelium increases (Yabuki et al 1999(Yabuki et al , 2003. In mice older than two years the incidence decreases (Okada et al 2005) (Fig. 4.60a & b).…”
Section: Urinary Systemmentioning
confidence: 95%